Electrochemical mechanism of cobalt film electrodeposition process. (6th June 2016) - Yu, Yundan; Song, Zhenlun; Ge, Hongliang; Wei, Guoying; Jiang, Li
Abstract : Cobalt films were electrodeposited on glassy carbon surface in the experiment to study the electrochemistry mechanism. Cobalt electrodeposition process was investigated by cyclic voltammetry, chronoamperometry, polarization curves and so on. It was found that cobalt started to deposit combined with hydrogen evolution at −0.3 VSCE . Hydrogen evolution was dominated from −0.3 to −0.9 VSCE . However, with the voltages increased from −0.9 to −1.1 VSCE, cobalt deposition was predominated. Cyclic voltammetry curves with different scan rates indicated that cobalt deposition was a kind of irreversible and diffusion-controlled process. According to typical nucleation model promoted by Scharifker and Hills, the results from chronoamperometry curves verified that cobalt electrodeposition on glassy carbon belonged to three-dimensional models with instantaneous nucleation. Cobalt films were a kind of grain films with typical nodular structures because of three-dimensional instantaneous nucleation mechanism.